P03.04 The impact of universal chlamydia trachomatis (ct) screening during pregnancy on seroepidemiology of chlamydial infection in american children, 1991–2013. (13th September 2015) - Banniettis, N; Szigeti, A; Sharma, S; Chotikanatis, K; Hammerschlag, MR; Kohlhoff, S
Abstract : Introduction: CT remains the most prevalent sexually transmitted infection in developed and developing countries. Prenatal screening and treatment of pregnant women has resulted in a dramatic decrease of perinatal CT l infection (conjunctivitis, pneumonia) in the US. Before the implementation of screening, ~50% of infants born to mothers with CT infection developed chlamydial conjunctivitis and/or pneumonia. However, there have been no studies of the incidence of perinatal CT infection, including seroepidemiologic studies, following the implementation of screening and treatment as recommended by the CDC in 1993. Methods: Anonymized banked serum and prospectively collected samples from children in Brooklyn, NY, were tested for CT IgG using the MIF assay. Serum samples were divided into 2 groups: 1: collected from 1991–1995, 2: from 2001–2013. Pts with C. pneumoniae (CP) infection (culture and/or antibody) were excluded. Results: 491 serum samples were identified (age range 0–20), 71 samples were excluded due to evidence of CP infection. 34% of subjects <10 y in group 1 (pre-universal screening) had IgG against CT, while there were no positives in group 2 (post-universal screening), p < 0.0001. Children >10 y had a prevalence of 32% in group 1 and 3.48% in group 2, p < 0.0001. Conclusion: Children <10 yr in group 1 (pre-screening) had relatively high rates of seropositivity, which were likely due to perinatal infection. This antibody was not due to CP, as sera from children with CP infection were excluded. The significantly lower rates in group 2 (post-screening) confirm that prenatal screening and treatment of pregnant women has been effective  for prevention of CT infection in infants. Persistence of antibody after perinatal infection may have implications for CT vaccine use in countries where prenatal screening and treatment has not been implemented.